Main regulatory factors of marbling level in beef cattle - Don V. Nguyen (Elsevier, 2021)
ABSTRACT: The content of intramuscular fat (IMF), that determines marbling levels is considered as one of the vital factors influencing beef sensory quality including tenderness, juiciness, flavour and colour. The IMF formation in cattle commences around six months after conception, and continuously grows throughout the life of the animal. The accumulation of marbling is remarkably affected by genetic, sexual, nutritional and management factors. In this review, the adipogenesis and lipogenesis process regulated by various factors and genes during fetal and growing stages is briefly presented. We also discuss the findings of recent studies on the effects of breed, gene, heritability and gender on the marbling accumulation. Various research reported that feeding during pregnancy, concentrate to roughage ratios and the supplementation or restriction of vitamin A, C, and D are crucial nutritional factors affecting the formation and development of IMF. Castration and early weaning combined with high energy feeding are effective management strategies for improving the accumulation of IMF. Furthermore, age and weight at slaughter are also reviewed because they have significant effects on marbling levels. The combination of several factors could positively affect the improvement of the IMF deposition. Therefore, advanced strategies that simultaneously apply genetic, sexual, nutritional and management factors to achieve desired IMF content without detrimental impacts on feed efficiency in high-marbling beef production are essential.